SINTESIS STEARAMIDA DARI ASAM STEARAT DAN UREA MENGGUNAKAN PELARUT CAMPURAN : PENGARUH TEMPERATUR DAN WAKTU REAKSI - Muhammad Syukri, Zuhrina Masyithah (Jurnal Teknik Kimia USU, 2018)
Surfactant is a molecule which has hydrophilic group and a lipophilic group which can unify a mixture consisting of water and oil. Stearamide is one kind of surfactant non-ionic which has used on any aplication. This study aims to know about optimum of temperature and time on synthesis of stearamide from stearic acid and urea with zirconium (IV) chloride in mixed solvent. This study will be observed the effect of temperature and reaction time on the synthesis of stearamide surfactant from stearic acid and urea with zirconium (IV) chloride as catalyst in mixed solvent. This research was conducted at temperature of 45°C, 55°C, 65°C, 75°C, 85°C and 95°C, reaction time of 1 hr, 2 hr, 3 hr, 4 hr, 5 hr, 6 hr, 7 hr and 8 hr, substrate molar ratio at 1:6 (w/w), solvent ratio at 2:1 (v/v), weight of catalyst 3% (%w), and stirring speed at 250 rpm. Based on this research, the optimum condition to synthesis stearamide surfactant was obtained at 85 oC and reaction time at 3 hours.